2021
DOI: 10.15537/smj.2021.42.9.20210224
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer associated with COVID-19 in Saudi Arabia

Abstract: with Coronaviruses disease-19 (COVID-19) infection who presented initially with gastrointestinal symptoms. The novel COVID-19 disease does not only affect the respiratory tract but also affects other parts of the body. A 23-year old male patient came to the emergency room suffering from acute abdominal pain and vomiting. The patient appeared to have a complicated course of infection with gastrointestinal manifestations and a perforated duodenal ulcer without any respiratory symptoms. Laboratory and radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 10 publications
0
12
0
8
Order By: Relevance
“…Medical colleagues from the Kingdom of Saudi Arabia have also reported such effects. [20] However, all the patients in this study were negative for SARS-CoV-2 infection, so peptic ulcers were not directly caused by the virus. Of course, some researchers have already found that in addition to symptoms caused by infection, indirect effects of the pandemic are also prevalent.…”
Section: Discussionmentioning
confidence: 86%
“…Medical colleagues from the Kingdom of Saudi Arabia have also reported such effects. [20] However, all the patients in this study were negative for SARS-CoV-2 infection, so peptic ulcers were not directly caused by the virus. Of course, some researchers have already found that in addition to symptoms caused by infection, indirect effects of the pandemic are also prevalent.…”
Section: Discussionmentioning
confidence: 86%
“…The grey literature search located no additional sources. Altogether, the evidence in this review includes 117 case reports/series 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 28 observational studies 10 , 11 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163...…”
Section: Resultsmentioning
confidence: 99%
“…According to studies, H. pylori infection is the main cause of PUD. However, recent studies have shown a relationship between SARS-CoV-2 and peptic ulcers [ 14 , 15 ]. Also, the symptoms of PUD include epigastric pain, heartburn, indigestion, and blood in the stool, while the pain usually occurs shortly after eating or when hungry [ 15 ].…”
Section: Discussionmentioning
confidence: 99%